Surgical treatment of spinal tumors with modified laminoplasty: Preliminary study - Surgical treatment of spinal tumors with modified laminoplasty: Preliminary study (International Journal of Spine Research - Peertechz Publications, 2022)
Objective: We aimed to present our experience with a modified laminoplasty technique that allows stabilization of the spine without instrumentation during tumor surgery.  Methods: This retrospective study was performed in the neurosurgery department of a university hospital and data were collected from the medical files who were treated surgically for spinal tumors. The same surgical team operated on the patients using the same procedure without any instrumentation for stabilization of the spine. Demographic and clinical data were collected. It was checked whether radiological and clinical instability developed at the 6th and 12th months postoperatively. Results: Our series comprised 41 patients (20 females, 21 males) with an average age of 47.122±20.33 (range: 11 to 86 years). The most common complaints detected in this series were diminution of motor power in lower extremities (20,47.62%), radicular pain (9,21.43%), and hypoesthesia (2,4.76%). The most frequent sites of involvement were L1-L2 (5,11.90%), L2 (4,9.52%), and T5-T6-T7 (2,4.76%), respectively. Histopathologically, schwannoma (8,19.94%), ependymoma (7,16.64%), meningioma (6,14.28%), and metastatic carcinoma (5,11.90%). The distribution of tumors was intradural and extramedullary (27,64.28%), intradural and intramedullary (13,30.95%), and extradural and extramedullary (2,4.77%), respectively.  Conclusion: Our results imply that stability of the spinal cord can be preserved without fixation or instrumentation during surgical procedures for spinal tumors. However, longer periods of follow-up, as well as prospective, controlled, multi-centric trials on larger populations, are warranted to evaluate the safety and efficacy of the novel technique.